Penyuluhan Budidaya Ikan Air Tawar di Desa Talang Jangkang, Kebupaten Indragiri Hilir - I, Ismandianto; Tri Arta, Adito; Sundari, Wanda; E, Egawirdawati; Nisa, Khairun; Erlangga, Friski; Zalianti, Tiara Putri; Agustin, Enda Suci; Pratama, Satryo Fadly; Antoto, Dirham; Siagian, Gita Trinatalis (Yayasan Daarul Huda Kruengmane, 2024)
Talang Jangkang Village is one of 11 villages in Kemuning District, Indragiri Hilir Regency. The Talang Jangkang area has a good water source that flows from the Reteh River. However, the potential for fisheries, especially fisheries cultivation, has not been optimal and well managed. In Talang Jangkang Village, there are only 39 freshwater fish cultivation ponds but they do not last long because many fish die and many also experience crop failures. The purpose of this freshwater cultivation extension activity is so that the people of Talang Jangkang Village are able to cultivate freshwater fish better and more precisely so that mistakes do not occur that cause fish to fail to harvest and mass deaths. The activity methods include program socialization, community group extension, and mentoring. The community group extension activity was carried out on August 13, 2024. The material provided includes Fish Enlargement, Water Quality Management, Feeding, Pest and Disease Control, and Harvesting. The community service team plays a role in providing an introduction to the discussion. After that, it was continued with a two-way discussion that placed the community as a subject who was actively involved in the extension activity. After the outreach activities were held, the community of Talang Jangkang Village increased their insight regarding freshwater fish cultivation.